Incidence and Risk Factors of Contrast Induced Nephropathy in Patients Following Coronary Angiography - Anwar, Mohammed Rashed; Hai, Abu Noim Md Abdul; Debnath, Dilip Kumar; Faraji, Md Anwarul Hoque; Hasan, KAM Mahbub (Journal of Science Foundation, 2018)
Background: Contrast induced nephropathy (CIN) is a common complication after administration of contrast medium. As the third leading cause of hospital acquired acute kidney injury, CIN occurs in half of the patients undergoing coronary angiography (CAG). Objective: The purpose of the present study was to see the frequency of contrast induced nephropathy in patients after coronary angiography and its risk factors. Methodology: This comparative cross sectional study was performed at National Institute of Kidney Diseases and Urology, Dhaka and Department of Cardiology, Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh from July, 2016 to December 2016 for a period of six (06) months. All patients 18 years and above who underwent coronary angiography with or without percutaneuous Transluminal coronary angioplasty with normal or impaired renal function, with or without Diabetes Mellitus or hypertension were included in the study. The patients were divided into two groups named as group A who did not develop CIN and group B developed CIN. Pre- and Post procedure serum creatinine was estimated at 48 hours after coronary angiogram. Independent characteristics associated with CIN were identified. Results: A total number of 250 patients were recruited for this study. Older age ≥70 years, diabetes mellitus were significant risk factor for CIN whereas hypertension was not statistically significant. Logistic regression analysis of risk factors were identified 05 (five) risk factors in this study which were baseline estimated GFR <60mi/min/1.73m2 BSA, diabetes mellitus, contrast volume >100ml, PTCA and LVEF < 40%). Effect of drugs used in the development of CIN by logistic regression analysis. None of the drugs showed significant relationship on development of CIN. Conclusion: Older age, baseline estimated GFR <60mi/min/1.73m2 BSA, diabetes mellitus, contrast volume >100ml, PTCA and LVEF < 40%) were significant risk factor to developed CIN. Journal of Science Foundation 2017;15(1):20-25